Report...to the National Assembly of Guyana, July 17, 1999, Georgetown, Guyana (The Commission GeorgetownGY, 1999)
States the context, methodology and process. Summarises the public submissions for the proposed constitution and dimensions considered by the Commission. Provides recommendations, supporting arguments and the votes for each proposed area of change.
DC